Soil cadmium extraction in Chinese cabbage and cabbage intercropping - Wan,Jiayue (2019)
ABSTRACT: Toxic metals contamination of soil has become a serious problem in recent years. In this study, Chinese cabbage (a relatively high-accumulator of cadmium (Cd)) and cabbage (a relatively low-accumulator of Cd) were cultured in monoculture and in intercropping in the Cd-contaminated soil, to evaluate the effect of intercropping on the alteration of Cd extraction. Both the pot experiments and field experiments indicated that intercropping increased the Cd extraction by Chinese cabbage and decreased the Cd extraction by cabbage. Thus, Cd extraction was advanced while safe production was obtained. Further pot experiment was conducted to investigate the alterations of soil Cd fractions, soil pH, and soil enzyme activities to reveal their possible relationship with Cd extraction between different planting patterns. Results revealed that three individual Chinese cabbages in one intercropping pot played the same effect on alteration of these factors as six individual Chinese cabbages in one monoculture pot. The intercropping increased Cd extraction by Chinese cabbage and decreased Cd extraction by cabbage, probably by influencing mechanisms such as soil enzyme activities (especially the urease activity) in the cultivation system. Effect of intercropping on Cd accumulation is an important issue in cultivation of vegetables in potentially contaminated land.